Treatment with radiosynoviorthesis in hemophilic patients with and without inhibitor - Mario Edgar Tena-Sanabria; Yoriko Fabiola Rojas-Sato; José Carlos Castañeda-Resendiz; Gabriela Fuentes-Herrera; Félix Alejandro Álvarez-Martínez; Yureni Iraí Tena-Gonzalez; Juan Carlos Núñez-Enríquez (BMC, 2020)
Abstract Background Spontaneous bleedings occurring into joints (hemarthrosis) are the most common manifestations of hemophilia and causes severe joint damage ultimately resulting in joint disfunction known as hemophilic arthropathy. Among available therapeutic options for reducing recurrent hemarthrosis-associated damage, radiosynoviorthesis (RS) has proven effective in improving joint function. Aim To assess the impact of RS with Yttrium(90) citrate (C-Y(90)) on frequency of hemarthroses and joint function in a group of pediatric patients. Methods Between November 1998 and February 2017, we evaluated 27 pediatric patients with mild, moderate or severe hemophilia with haemophilic arthropathy. Overall, RS was applied in 60 joints. Some patients received more than one single intra-articular injection with C-Y(90). Results During the follow-up, one patient showed joint bleeding 15 months after RS, one patient after 12 months and one patient after 45 days. The episodes of hemarthrosis were reduced and joint function significantly improved in all patients. Conclusion RS with C-Y(90) is a simple and safe treatment for reducing the frequency of hemarthroses in patients with hemophilia. It decreases the use of factor VIII / IX and improves joint function.